Data sharing practices in randomized trials of addiction interventions. (March 2020) - Vassar, Matt; Jellison, Sam; Wendelbo, Hannah; Wayant, Cole
Highlights: No investigation of data sharing practices in published addiction medicine trials has been conducted. We found that zero included addiction medicine trials shared their data publicly. The implications may include delays to scientific progress or self-correction, as well as a breach of social contracts to the public, who funded the majority of included trials. Abstract: Introduction: Transparent, open scientific research practices aim to improve the validity and reproducibility of research findings. A key component of open science is the public sharing of data and metadata that constitute the basis for research findings. Methods: We conducted a 6 year cross-sectional investigation of the rates and methods of data sharing in 15 high-impact addiction journals that publish clinical trials. We extracted trial characteristics and whether the trial data were shared publicly in any form. We conducted a sensitivity analysis of only trials with public funding sources. Results: In the included journals, zero (0/394, 0.0%) RCTs shared their data publicly. The large majority (315/394, 79.9%) of included trials received funding from public sources. Eight journals had data sharing policies and published 299 of the included trials (75.9%). Conclusion: Our finding has significant implications for the addiction research community. These implications are broad, ranging from possibly slowed scientific advancement to noncompliance with obligations to the public whose tax dollars funded a large majority of the included RCTs. To improve the rates of data sharing, we recommend studying incentive systems, while simultaneously working to cultivate a data sharing system that emphasizes scientific, rather than author, accuracy.